More trade for better health? International trade and tariffs on health products - Matthias Helble (World Trade Organization (WTO), 2012)
The main objective of this paper is to analyse trade flows and tariff policies of health products. Compared to previous studies, we not only focus on medicines, but on a large set of products that enter the public health space and can be identified in the common trade classification. The first contribution is thus to construct three groups of health products based on the 2007 Harmonized System classification of international trade. Using these commodity groups, we analyse trade flows between 167 countries for the years 1996 to 2009. We find that trade in health products has developed very dynamically, with trade in dosified medicine displaying the strongest growth with an annual growth rate of almost 12 per cent. The results further indicate that the market of health products is dominated by a small number of developed countries. Looking at tariffs on health products for developed and developing countries as well as LDCs and transition economies we find that the overall level of tariffs is low, but far from being zero, especially in the last three country groups. Finally, studying the tariffs on health products in preferential trade agreements between developing countries, the results show that the tariff level is low, but in some individual cases still substantive.
Keywords: F14; I11; O24; 330; Public health; tariffs; trade; pharmaceuticals; medical devices; medical technology; Gesundheitswesen; Außenhandel; Zoll